STRATEGI METODE UJI TASMI’ PADA PROGRAM TAHFIDZ PONDOK PUTRI HAFSHAWATY TIMUR PESANTREN ZAINUL HASAN GENGGONG PROBOLINGGO - Nadhifah, Diana; Khumaidi, Ahmad; Zaini, Bahruddin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The tasmi’ test method is an effective strategy for strengthening Qur’anic memorization among tahfidz program students. This study aims to examine the implementation strategy of the tasmi’ test method in the tahfidz program at Putri Hafshawaty East Islamic Boarding School, Zainul Hasan Genggong Probolinggo. The method is used as an evaluation tool to monitor and appreciate the memorization achievements of students due to its ease of application. This study employs a qualitative approach with data collection techniques including observation and interviews. The subjects are tahfidz program students actively participating in the tasmi’ test method. The results indicate that the tasmi’ test method strategy enhances students’ perseverance and motivation to increase their memorization. Additionally, the method highlights the important role of the listener (teacher/ustadzah) as a facilitator who creates a supportive and conducive learning environment for all students at the boarding school. Therefore, the implementation of the tasmi’ test method strategy has proven effective in improving the memorization quality of tahfidz students at Putri Hafshawaty East Islamic Boarding School.